Relationship between magnetic properties and microstructure of ferrites during sintering in radiation and radiation-thermal conditions - Malyshev, A.V.; Lysenko, Е.N.; Sheveleva, E.A.; Surzhikova, O.A.; Aringazin, A.K. (KU publ., 2021)
The studies of correlation between magnetic properties and microstructure were conducted on samples of lithium-substituted ferrite, sintered in radiation and radiation-thermal conditions. Radiation-thermal sintering was performed for compacts irradiated with a pulsed electron beam with energy of (1.5–2.0) MeV, beam current per pulse of (0.5-0.9) A, irradiation pulse duration of 500 μs, pulse repetition rate of (5–50) Hz, and compact heating rate of 1000 C/min. Sintering in thermal furnaces (T-sintering) was carried out in a preheated chamber electric furnace. The paper shows that magnetic induction does not depend on the ferrite grain size. In this case, the coercive force is inversely proportional to the grain size and depends on the intragranular porosity of ferrite samples. In contrast to thermal sintering, radiation-thermal sintering does not cause capturing of intergranular voids by growing grains and enhances coagulation of intragranular pores.
Радиациялық және радиациялы-термиялық жағдайларда қақтау кезінде ферриттердің магниттік қасиеттері мен микроқұрылымының өзара байланысы
Взаимосвязь магнитных свойств и микроструктуры ферритов при спекании в радиационных и радиационно-термических условиях.
Keywords: ferrites; sintering; magnetic properties; microstructure; intense electron beams; high temperatures